Myeloid Immune Cells CARrying a New Weapon Against Cancer - Ramos, Rodrigo Nalio; Couto, Samuel Campanelli Freitas; Oliveira, Theo Gremen M.; Klinger, Paulo; Braga, Tarcio Teodoro; Rego, Eduardo Magalhães; Barbuto, José Alexandre M.; Rocha, Vanderson (Frontiers in Cell and Developmental Biology, 2021)
Chimeric antigen receptor (CAR) engineering for T cells and natural killer cells (NK) are now under clinical evaluation for the treatment of hematologic cancers. Although encouraging clinical results have been reported for hematologic diseases, pre-clinical studies in solid tumors have failed to prove the same effectiveness. Thus, there is a growing interest of the scientific community to find other immune cell candidate to express CAR for the treatment of solid tumors and other diseases. Mononuclear phagocytes may be the most adapted group of cells with potential to overcome the dense barrier imposed by solid tumors. In addition, intrinsic features of these cells, such as migration, phagocytic capability, release of soluble factors and adaptive immunity activation, could be further explored along with gene therapy approaches. Here, we discuss the elements that constitute the tumor microenvironment, the features and advantages of these cell subtypes and the latest studies using CAR-myeloid immune cells in solid tumor models.